Cardioprotective Potential of Human Endothelial-Colony Forming Cells from Diabetic and Nondiabetic Donors - Marcus-André Deutsch; Stefan Brunner; Ulrich Grabmaier; Robert David; Ilka Ott; Bruno C. Huber (Cells, 2020)
Objective: The potential therapeutic role of endothelial progenitor cells (EPCs) in ischemic heart disease for myocardial repair and regeneration is subject to intense investigation. The aim of the study was to investigate the proregenerative potential of human endothelial colony-forming cells (huECFCs), a very homogenous and highly proliferative endothelial progenitor cell subpopulation, in a myocardial infarction (MI) model of severe combined immunodeficiency (SCID) mice. Methods: CD34+ peripheral blood mononuclear cells were isolated from patient blood samples using immunomagnetic beads. For generating ECFCs, CD34+ cells were plated on fibronectin-coated dishes and were expanded by culture in endothelial-specific cell medium. Either huECFCs (5 × 105) or control medium were injected into the peri-infarct region after surgical MI induction in SCID/beige mice. Hemodynamic function was assessed invasively by conductance micromanometry 30 days post-MI. Hearts of sacrificed animals were analyzed by immunohistochemistry to assess cell fate, infarct size, and neovascularization (huECFCs n = 15 vs. control n = 10). Flow-cytometric analysis of enzymatically digested whole heart tissue was used to analyze different subsets of migrated CD34+ /CD45+ peripheral mononuclear cells as well as CD34−/CD45− cardiac-resident stem cells two days post-MI (huECFCs n = 10 vs. control n = 6). Results: Transplantation of human ECFCs after MI improved left ventricular (LV) function at day 30 post-MI (LVEF: 30.43 ± 1.20% vs. 22.61 ± 1.73%, p < 0.001; ΔP/ΔTmax 5202.28 ± 316.68 mmHg/s vs. 3896.24 ± 534.95 mmHg/s, p < 0.05) when compared to controls. In addition, a significantly reduced infarct size (50.3 ± 4.5% vs. 66.1 ± 4.3%, p < 0.05) was seen in huECFC treated animals compared to controls. Immunohistochemistry failed to show integration and survival of transplanted cells. However, anti-CD31 immunohistochemistry demonstrated an increased vascular density within the infarct border zone (8.6 ± 0.4 CD31+ capillaries per HPF vs. 6.2 ± 0.5 CD31+ capillaries per HPF, p < 0.001). Flow cytometry at day two post-MI showed a trend towards increased myocardial homing of CD45+ /CD34+ mononuclear cells (1.1 ± 0.3% vs. 0.7 ± 0.1%, p = 0.2). Interestingly, we detected a significant increase in the population of CD34−/CD45−/Sca1+ cardiac resident stem cells (11.7 ± 1.7% vs. 4.7 ± 1.7%, p < 0.01). In a subgroup analysis no significant differences were seen in the cardioprotective effects of huECFCs derived from diabetic or nondiabetic patients. Conclusions: In a murine model of myocardial infarction in SCID mice, transplantation of huECFCs ameliorated myocardial function by attenuation of adverse post-MI remodeling, presumably through paracrine effects. Cardiac repair is enhanced by increasing myocardial neovascularization and the pool of Sca1+ cardiac resident stem cells. The use of huECFCs for treating ischemic heart disease warrants further investigation.